Insulator-metal transition and quasi-flat-band of Shastry–Sutherland lattice. (5th June 2019) - Huang, Huai-Xiang; Chen, Jing; Ren, Wei; Gao, Yi; Li, Wei; Chen, Yan
Abstract: Insulator-metal transition is investigated self-consistently on the frustrated Shastry–Sutherland lattice in the framework of Slave-Boson mean-field theory. Due to the presence of quasi-flat band structure characteristic, the system displays a spin-density-wave (SDW) insulating phase at the weak doping levels, which is robust against frustration, and it will be transited into an SDW metallic phase at high doping levels. As further increasing the doping, the temperature or the frustration on the diagonal linking bonds, the magnetic order m will be monotonically suppressed, resulting in the appearance of a paramagnetic metallic phase. Although the Fermi surface of the SDW metallic phase may be immersed by temperature, the number of mobile charges is robust against temperature at weak doping levels.